2006
DOI: 10.1152/japplphysiol.01538.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of load carrying on metabolic cost and hindlimb muscle dynamics in guinea fowl (Numida meleagris)

Abstract: The goal of this study was to test whether the contractile patterns of two major hindlimb extensors of guinea fowl are altered by load-carrying exercise. We hypothesized that changes in contractile pattern, specifically a decrease in muscle shortening velocity or enhanced stretch activation, would result in a reduction in locomotor energy cost relative to the load carried. We also anticipated that changes in kinematics would reflect underlying changes in muscle strain. Oxygen consumption, muscle activation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
37
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 46 publications
13
37
1
Order By: Relevance
“…2 and Table 1). Running guinea fowl similarly show no change in MG fascicle velocity with running speed (16). These data support the assumption of Kram and Taylor (26) that muscles are working on a similar part of their force-velocity relationship across all steady-state running speeds.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…2 and Table 1). Running guinea fowl similarly show no change in MG fascicle velocity with running speed (16). These data support the assumption of Kram and Taylor (26) that muscles are working on a similar part of their force-velocity relationship across all steady-state running speeds.…”
Section: Discussionsupporting
confidence: 84%
“…Using sonomicrometry and tendon buckle transducers, Prilutsky et al (15) showed that the velocity of cat gastrocnemius fibers increased with walking speed, impairing gastrocnemius force production at faster speeds. In running guinea fowl (16) and turkeys (17), ankle extensors operate at low fascicle-shortening velocities, supporting the notion that running gait allows distal leg muscles to operate under favorable conditions for force production. However, these animal data come from varied species and may not translate well to humans.…”
mentioning
confidence: 59%
“…Note that the stance active ILPO can itself be considered a neuromuscular compartment of the iliotibialis lateralis because in most species it is contiguous with the iliotibialis lateralis preacetabularis, which is active during swing phase (Gatesy, 1999b). Whether further differences in function occur along the anterior-posterior axis within the ILPO has not been revealed in previous studies (Buchanan, 1999;McGowan et al, 2006;Roberts et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The function of substantial active lengthening of this large muscle is not clear. Other researchers have suggested that the active lengthening-shortening cycle might enhance economy of force production (McGowan et al, 2006;Roberts et al, 2007). However, active lengthening of muscle fibers beyond their short-range elasticity absorbs work that cannot be recovered, and replacing this negative work could increase the cost of legged locomotion (see Discussion).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have demonstrated that during running the ILPO in the guinea fowl and turkey actively lengthens and absorbs work during the first part of stance, then actively shortens to produce work during the latter half of stance (Buchanan, 1999;Marsh, 1999;McGowan et al, 2006;Roberts et al, 2007). The function of substantial active lengthening of this large muscle is not clear.…”
Section: Introductionmentioning
confidence: 99%